(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Acute diseases of the abdominal organs remain one of the most common causes of emergency hospitalization and urgent surgical interventions. A significant clinical challenge is represented by patients with an unclear or atypical clinical presentation, in whom conventional diagnostic methods—clinical examination, laboratory tests, ultrasonography, and computed tomography—do not always allow timely establishment of an accurate diagnosis and determination of optimal treatment strategy. Diagnostic errors and delayed verification of the disease often lead to progression of the pathological process, development of complications, and deterioration of treatment outcomes. Under these conditions, emergency laparoscopy acquires particular importance as a highly informative and minimally invasive method that enables direct visualization of the abdominal organs, clarification of the nature and extent of pathological changes, and, in many cases, immediate transition from diagnosis to treatment. The use of laparoscopy contributes to a reduction in the number of unjustified laparotomies, shorter hospital stays, and a lower incidence of postoperative complications.